Perspectives on oral chronic graft-versus-host disease from immunobiology to morbid diagnoses - Tollemar, Victor; Garming Legert, Karin; Sugars, Rachael V. (Frontiers in Immunology, 2023)
Chronic Graft-versus-Host Disease (cGVHD) is a major long-term complication, associated with morbidity and mortality in patients following allogenic hematopoietic cell transplantation (HCT) for immune hematopoietic disorders. The mouth is one of the most frequently affected organs after HCT (45-83%) and oral cGVHD, which may appear as the first visible sign. Manifestations present with mucosal lichenoid lesions, salivary gland dysfunction and limited oral aperture. Diagnosis of oral cGVHD severity is based on mucosal lesions with symptoms of sensitivity and pain and reduced oral intake. However, diagnostic difficulties arise due to subjective definitions and low specificity to cover the spectrum of oral cGVHD. In recent years there have been significant improvements in our understanding of the underlying oral cGVHD disease mechanisms. Drawing upon the current knowledge on the pathophysiology and biological phases of oral cGVHD, we address oral mucosa lichenoid and Sjogren’s Syndrome-like sicca syndromes. We consider the response of alloreactive T-cells and macrophages to recipient tissues to drive the pathophysiological reactions and biological phases of acute inflammation (phase 1), chronic inflammation and dysregulated immunity (phase 2), and subsequent aberrant fibrotic healing (phase 3), which in time may be associated with an increased malignant transformation rate. When formulating treatment strategies, the pathophysiological spectrum of cGVHD is patient dependent and not every patient may progress chronologically through the biological stages. As such there remains a need to address and clarify personalized diagnostics and management to improve treatment descriptions. Within this review, we highlight the current state of the art knowledge on oral cGVHD pathophysiology and biological phases. We address knowledge gaps of oral cGVHD, with a view to facilitate clinical management and improve research quality on lichenoid biology and morbid forms of oral cGVHD.